Prevalence and Antibiotic Resistance Patterns of Ocular Bacterial Strains Isolated from Pediatric Patients in University Hospital of Campania “Luigi Vanvitelli,” Naples, Italy - Francesco Petrillo; Veronica Folliero; Biagio Santella; Gianluigi Franci; Francesco Foglia; Maria C. Trotta; Maria T. Della Rocca; Teresio Avitabile; Caterina Gagliano; Marilena Galdiero (International Journal of Microbiology)
Eye infections caused by bacteria are a serious public health problem among pediatric patients. These diseases, if not properly treated, can cause blindness and impaired vision. The study aimed to evaluate the antimicrobial resistance profiles of the main pathogens involved in eye infections. This study involved pediatric patients enrolled at the “Luigi Vanvitelli” University Hospital of Campania in Naples, Italy, between 2017 and 2019. Of a total of 228 pediatric patients, 73 (32%) tested positive for bacterial infection. In terms of strain distribution, 85% were Gram-positive bacteria, while 15% were Gram-negative bacteria. The most frequently isolated strains were coagulase-negative Staphylococci (60.4%), followed by Staphylococcus aureus (16.4%). The isolated bacteria showed a significant percentage of resistance to multiple antibiotics. Therefore, the identification of the causal bacteria and antimicrobial sensitivity tests are mandatory to select the effective drug for the treatment of eye infections and prevent the development of antibiotic-resistant bacteria.